Trends, Risk Factors and Treatment of Common Cancers: Outcome of Hospital Based Survey Conducted in Dhaka, Bangladesh - Nurunnabi, Abu Sadat Mohammad; Asaduzzaman, Mohammad; Alam, Mohammad Jahangir; Sultana, Most Rokaya; Alamgir, Sadia Nusrat (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: In Bangladesh, the estimated incidence of 12.7 million new cancer cases will rise to 21.4 million by 2030. Objective: The study aims to provide information about the common cancer types, predisposing risk factors and modalities of treatment among the Bangladeshi cancer patients. Methods: This cross-sectional, descriptive study was conducted between July and December of 2014, in different cancer hospitals located in Dhaka city, Bangladesh. Interviews were conducted based on a semi-structured questionnaire with 550 histopathologically confirmed cancer patients or patients having radio-pathological and clinical evidence of cancer (339 men and 211 women). Results: Among the male patients, the leading cancers were lung (23%), followed by mouth and oropharynx (16.52%), stomach (14.45%), colorectal (10.91%) cancers and others (35.12%). Among the female, breast cancer (31.75%) was the highest, followed by cancer of cervix (27.96%), ovary (18%), mouth and oropharynx (13.27%), stomach (4.74%) and others (4.28%). Among the risk factors of male cancer patients, tobacco smoking was considered highest (76.4%), followed by chewing betel leaf and nuts (61.65%) and chronic disease (58.4%). Among women, the attributable fraction of cancer causing by recurrent STDs (37.91%) was found as the highest, followed by obesity (36.97%), chronic disease (32.7%), chewing betel leaf and nuts (23.22%) and tobacco smoking (26.54%). Main treatment modalities were surgery, chemotherapy and radiotherapy applied either individually or in combination. Most of the patients received chemotherapy (54.72%), followed by chemotherapy with radiation (32%). Only 7.81% patients got palliative care. Conclusion: There are resource-strained oncology units in different public hospitals along with few private hospitals in Dhaka. However, this survey revealed that many patients lack access to cancer awareness programme, cancer screening facilities, availability of low-cost drugs, therapies and palliative care. Hence, promotion of health education, behavioural change communication and development of treatment facilities and manpower are recommended. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 252-256